HUBUNGAN MINAT BELAJAR SEJARAH DAN PERSEPSI DENGAN PEMAHAMAN MATERI SEJARAH SISWA KELAS XI IPS SMA NEGERI SE-KOTA BANJARBARU - Rahmad Rahmad (JURNAL SOCIUS, 2013)
This research aims to know 1) is there any corelation between interest of learning history and understanding of Banjarese kingdom history material. 2) is there any corelation between perception toward understanding of Banjarese kingdom history material. 3) is there any correlation between interest in learning history and perception toward understanding of Banjarese kingdom history material of the eleventh grade social studies students in Banjarbaru. The sampling of this research uses proportional probability sampling are 195 students. Datum collected by using the questionnaire for the interest of learning history and perception variable, and use the test for comprehention variable. Based on this research, we can conclude: There is the positive and significant correlation between the interest of learning history (X1) and perception (X2) toward the eleventh grade social studies students’ understanding of Banjarese kingdom history material (Y)Key words: Interests Learning History, Perception, History of the Kingdom of Banjar